2014
DOI: 10.1002/jcu.22127
|View full text |Cite
|
Sign up to set email alerts
|

Doppler ultrasonographic evaluation of the radial and ulnar arteries in hemiparetic patients after stroke

Abstract: Hand blood flow was lower on the paretic side and was accompanied by a similar decrease in SSR amplitudes in patients with right-sided hemiparesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A systematic search resulted in 940 studies. After exclusions, 450 full-texts were screened resulting in 71 studies included in our meta-analysis with a total of 4886 patients 7 8 12–80. A PRISMA flowchart can be seen in online supplemental figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic search resulted in 940 studies. After exclusions, 450 full-texts were screened resulting in 71 studies included in our meta-analysis with a total of 4886 patients 7 8 12–80. A PRISMA flowchart can be seen in online supplemental figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…As for the stroke patients, some studies suggested that the blood flow of stroke patients on the affected limbs was lower than on the unaffected side. Tiftik et al [ 33 ] showed that the radial and ulnar arteries of the affected side were significantly smaller in volume flow and end-diastolic velocity. Billinger et al [ 42 ] found that the blood flow was also reduced in the femoral artery of the affected body.…”
Section: Discussionmentioning
confidence: 99%
“…Blood flow is one of the most important objective indicators for motor recovery. Several studies have demonstrated that motor function is related to tissue perfusion or blood flow in stroke patients [ 32 , 33 ]. As a general evaluation tool, laser speckle contrast imaging (LSCI) technology is recognized as a useful tool to determine skin blood flow (SkBF).…”
Section: Introductionmentioning
confidence: 99%
“…The blood flow velocities and waveforms in radial and ulnar arteries have been used to evaluate sympathetic skin response between healthy subjects and patients after stroke (Tiftik et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The methods used for estimating the flow rate in these studies estimates the flow rate simply through the product of maximum velocity and blood vessel area (Ozcan et al 2011;Toprak et al 2011;Tiftik et al 2014). Further, no consideration in the literature has been given to evaluate the accuracy or reliability of these measurements.…”
Section: Introductionmentioning
confidence: 99%